The Genre of Technological Procedure Text With A Systemic Functional Linguistics Approach - Sopha, Diana; Nurmala, Dewi; Ningsih, Ayu Melati (ITScience (Information Technology and Science), 2025)
In the current digital era, the rapid development of technology has resulted in the creation of increasingly sophisticated technological products. In the marketing of these products, the use of language is indispensable. Written language explaining the steps or stages of product use is called a procedural text genre. This text plays a vital role in product marketing because it contains essential information related to product explanations, making it easy for consumers to understand. This is what underlies the importance of conducting research on the function of language in terms of meaning and language structure in the genre of technological procedure texts. By applying a qualitative method, the research data in the genre of technological procedural texts is analysed based on its linguistic functions, covering aspects of meaning and language structure. In the research findings, three language functions were obtained, namely those that contain meaning: Command, Statement, and Prohibition. These three language functions are realised in language (text) in the form/structure: Imperative and Declarative. First, commands use the imperative structure. Second, statements are structured in the declarative form. Third, prohibitions are structured imperatively; fourth, commands are structured declaratively; and finally, fifth, prohibitions are structured declaratively.